ACTIVE BIOPACKAGING FROM DAMMAR FOR COMMINUTED MEAT PRESERVATION - Noryawati Mulyono; Asaf Kleopas Sugih (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
This research aimed to develop biopackaging materials using thermoplastic starch matrix and Indonesian dammar extracts possessing antimicrobial activity, i.e. flesh dammar (Shorea leprosula) and stone dammar (S. eximia), for preserving comminuted meat. The packaging matrix was prepared using continuous melt mixing of tapioca starch and glycerol in a co-rotating twin extruder. Subsequently, the matrix was dipped in dammar extracts, with or without the addition of antimicrobial agents such as propyl paraben, zinc chloride, zinc acetate, and silver nitrate. As a result, flesh dammar performed greater antibacterial activity than that of stone dammar. Moreover, the antibacterial activity of silver nitrate in the biopackaging was comparable to that of zinc chloride while combined with dammar, but zinc acetate was less effective. On the other hand, active biopackaging comprised of combination of dammar and propyl paraben was the least effective. Among the eight combinations of two dammar extracts and four antimicrobial agents, flesh dammar extract comprised of 0.1% (w/v) zinc chloride and 1.0% (w/v) lecithin was found as the most promising formulation for dipping with regard to its production cost and antimicrobial activity. Total plate count (TPC) in comminuted meat wrapped with active biopackaging (initial microbial load of 5.2 ± 0.1 × 104 CFU/g) decreased to 2.8 ± 0.1 × 104 CFU/g over 9 days of storage at 40°C temperature. This number was lower than TPC value of nitrate-preserved meat (3.4 ± 0.2 × 104 CFU/g and 5.9 ± 0.4 × 105 CFU/g, respectively).